Iron deficiency anaemia among 6-to-36-month children from northern Angola - Cláudia Fançony (BMC Pediatrics, 2020)
Abstract Background Angola is one of the southern African countries with the highest prevalence of anaemia. Identifying anaemia determinants is an important step for the design of evidence-based control strategies. In this study, we aim at documenting the factors associated with Iron Deficiency Anaemia (IDA) in 948 children recruited at the Health Research Center of Angola study area during 2015. Methods Data on demographic, socio-economic and parental practices regarding water, sanitation, hygiene, malaria infection and infant and young child feeding were collected, as well as parasitological, biochemical and molecular data. Total and age-stratified multivariate multinomial regression models were fitted to estimate the magnitude of associations between anaemia and its determinants. Results Anaemia was found in 44.4% of children, of which 46.0% had IDA. Overall, regression models associated IDA with age, gender and inflammation and non-IDA with age, zinc deficiency and overload, P. falciparum infection, sickle cell trait/anaemia. Among 6-to-23-month-old children IDA was associated with continued breastfeeding and among 24-to-36-month-old children IDA was associated with stunting. Furthermore, zinc deficiency was associated with non-IDA among both age groups children. Inflammation was associated with IDA and non-IDA in either 6-to-23 and 24-to-36 months old children. Conclusion The main variables associated with IDA and non-IDA within this geographic setting were commonly reported in Africa, but not specifically associated with anaemia. Additionally, the associations of anaemia with inflammation, zinc deficiency and infections could be suggesting the occurrence of nutritional immunity and should be further investigated. In age groups, zinc overload was observed to protect under 6 months children from Non-IDA, while continued breastfeeding was associated with increased IDA prevalence in 6-to-23 months children, and stunting was suggested to increase the odds of IDA in 24-to-36 month children. This site-specific aetiology profile provides an essential first set of evidences able to inform the planification of preventive and corrective actions/programs. Nevertheless, regional and country representative data is needed.